Impact of Library Collections on User Satisfaction: a case study. - Sivathaasan, N. (European Journal of Business and Management, 2013)
Academic library is the heart of any university which assists to conduct research programs successfully. Thestudy explores to identify the impact of library collections on user satisfaction of the students reading at theFaculty of Management Studies and Commerce of University of Jaffna. In the present study, library collections and user satisfaction are considered as independent variables and dependent variable respectively. The study wasanalyzed by using both primary and secondary data with 202 students. Results revealed that 11.1 % of usersatisfaction is determined by library collections according to the Regression analysis. This survey contributes tothe Library, University of Jaffna to strengthen the user satisfaction through collections and makes keyrecommendations.
Keywords: Library Collections; User Satisfaction; University of Jaffna